Critical mission : essays on democracy promotion - Carothers, Thomas, 1956- (Carnegie Endowment for International Peace, 2004)
Demand for practical knowledge and lessons about how the United States and other countries can more effectively promote democracy around the world has never been higher. This timely book by Thomas Carothers, one of the foremost authorities worldwide on democracy building, helps meet that need. Critical Mission draws together a wide-ranging set of Carothers's many seminal, widely cited essays, organized around four vital themes: the role of democracy promotion in U.S. foreign policy the core elements of democracy aid the state of democracy in the world the new U.S. push to promote democracy in the Middle East From puncturing myths about promoting civil society to sizing up the prospects for democracy in the Arab world, Carothers is consistently penetrating, incisive, and challenging to policymakers, democracy activists, and scholars alike. The book also includes the only up-to-date, comprehensive bibliography on democracy promotion.
Keywords: Democracy.; Democratization.; Economic assistance.; Democracy; Démocratie.; Démocratisation.; Aide économique.; assistance.; democracy.; POLITICAL SCIENCE -- General.; Democratization; Economic assistance; Democratie.; Democratisering.; Buitenlandse politiek.; 89.35 democracy.; Politique étrangère.; Etats-Unis d'Amérique.; Monde.; Außenpolitik; Demokratie; USA; United States of America.; Foreign policy.; International relations.; Development aid.